Experience of laparoscopic surgery in childrens in Instituto Especializado de Salud del Niño - Montes Chávez, Juan Carlos (2006)
The aim of this study was to know characteristics of recent technique advances on the safety and a benefit, using a retrospective evaluation, was performed successfully on 304 patients aged 1 month to 18 years. We study to pediatric patients underwent laparoscopy surgery at the Instituto Especializado de Salud del Niño, since their beginnings, on November 1999, to May 2004 and involves a review of medical records from Patients with the file card. More frequent operations were Explorer laparoscopy with hepatic biopsy (n= 78, 25,7%), varicocelectomy (n= 73, 24,1%), appendicectomy (n= 47, 15,5%), explorer laparoscopy (n= 33, 10,9%), cholecystectomy (n= 22, 7,3%), gonadal operations (n= 11, 3,6%), splenectomy (n= 7, 2,3%) besides: adhesions liberation, nephrectomies, hysterectomy, Nissen_fundoplication. The curent study shows that laparoscopy surgery is a safe and effective alternative to open surgery in children included emergency procedures.